2019
DOI: 10.18632/aging.102374
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent relationship between preoperative serum aminotransferase and mortality after cardiovascular surgery

Abstract: Although serum aminotransferase levels are frequently measured for preoperative evaluation, their prognostic value to postoperative outcomes remain unclear. This study aimed to investigate the relationship between preoperative serum aminotransferase levels and postoperative 90-day mortality in patients undergoing cardiovascular surgery. We included adult patients (n=6264) who underwent cardiovascular surgery between January 2010 and December 2016 at a tertiary academic hospital. Preoperative serum alanine amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 35 publications
(56 reference statements)
2
16
1
Order By: Relevance
“…The De Ritis ratio provided incremental values for risk prediction beyond clinical risk factors. These results are consistent with prior findings of the De Ritis ratio and a high mortality rate in critical illness and various types of cancers [ 6 , 7 , 18 , 19 ]. While in hematologic malignancies, the De Ritis ratio was reported only as an adverse event style after treatment [ 20 , 21 ], such as leukaemia and lymphoma, and its association with mortality has not been researched.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The De Ritis ratio provided incremental values for risk prediction beyond clinical risk factors. These results are consistent with prior findings of the De Ritis ratio and a high mortality rate in critical illness and various types of cancers [ 6 , 7 , 18 , 19 ]. While in hematologic malignancies, the De Ritis ratio was reported only as an adverse event style after treatment [ 20 , 21 ], such as leukaemia and lymphoma, and its association with mortality has not been researched.…”
Section: Discussionsupporting
confidence: 93%
“…The ratio of serum AST and ALT was initially described by De Ritis and has been known as the De Ritis ratio [ 5 ]. Over the past several decades, it has subsequently been shown to be a useful prognostic predictor in critical illness and malignant tumors, including acute myocardial infarction [ 6 ], cardiovascular surgery [ 7 ], metastatic renal cell carcinoma [ 8 ], and upper tract urothelial carcinoma [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…18 Serum aminotransferase levels are used for prognostic evaluation of cardiovascular surgery, particularly in the elderly. 19 Based on the pathological manifestations of COVID-19 patient's liver tissue, which showed moderate microvesicular steatosis and mild lobular activity, 20 we speculate that, in addition to adverse drug reactions, severe hypoxaemia, increased metabolic activity/ demand and passive congestion of the liver might contribute to the more abnormal liver function in COVID-19 patients with CVD, but the significance of these needs to be studied further.…”
Section: What Might This Study Add?mentioning
confidence: 97%
“…Coronavirus disease 2019 (COVID- 19), which was first reported in Wuhan, Hubei Province in December 2019, has since spread to the southwest region in an extremely short time. 1 The spread of the virus prompted Chinese officials to partially lock down major cities and strengthen public health interventions before the Spring Festival.…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that an ALT > 10 IU/L among elderly patients with hip fracture was associated with better functional and cognitive status, as shown by higher total FIM (Functional Independence Measure) scores, cognitive FIM scores (>16), and FIM efficiency (>0.228) in a logistic regression analysis adjusted for age and gender (OR = 1.56–1.78) [ 24 ]. In clinical cardiology, low ALT levels were associated with increased long-term mortality among 6575 middle-aged patients with stable coronary heart disease [ 38 ], increased 90-day mortality in 6264 patients undergoing cardiovascular surgery [ 39 ], and lower baseline fitness and poor rehabilitation outcomes amongst 3806 participants of a cardiac rehabilitation program [ 23 ]. As opposed to the conventional assessment of frailty, ALT plasma measurement does not require additional substantial resources such as work force, money, and time.…”
Section: Discussionmentioning
confidence: 99%